Digitizing Cultural Heritage of Nepal: Tools for Conservation and Restoration - Ghimire, Prashamsa (Unity Journal, 2023)
Our identity as a human being is a result of generations of handed-down culture and traditions. The definition with which we identify today as a society, as a community, as a nation and as a world all dates back to time immemorial. Be it the 2015 Earthquake that hit Nepal and shattered most of our preserved monuments or the stolen artifacts which are sold for millions to foreign countries illegally, every passing day, our identity as Nepalese is threatened. With little importance paid to the ‘actual conservation’ of our temples, monuments, arts and crafts, this paper calls for sensitivity towards a cultural emergency. While problems exist, solutions have been adopted in the past, like the 3-D Laser Scanning of Pancha Deval Temple or the efforts made by National Heritage Documentation Project for constructing a wide-ranging digital records of historical artistic monuments in the danger of extinction. To preserve the roots of our forefathers, we should ramp up the process of utilizing available technology. With the evolution of technology, we have many resources to take inspiration from. Digitization of Cultural and National Heritage will help secure our original heritage in the finest of the finest circumstances. With the aid of technologies like Machine Algorithms, Laser scanning and many more not only the physical structure of the heritage can be preserved but also the age long history behind the heritage will be intact. The following paper outlines some possibilities of using new technologies in the heritage of Nepal and possibilities to explore further.